Feasibility of measuring superior mesenteric artery blood flow during cardiac surgery under hypothermic cardiopulmonary bypass using transesophageal echocardiography: An observational study - Naveen G Singh; P S Nagaraja; Divya Gopal; V Manjunath; K S Nagesh; N Manjunatha; Guru Police Patel; Satish Kumar Mishra (Annals of Cardiac Anaesthesia, 2016)
Background: Abdominal complications being rare but results in high mortality, commonly due to splanchnic organ hypoperfusion during the perioperative period of cardiac surgery. There are no feasible methods to monitor intraoperative superior mesenteric artery blood flow (SMABF). Hence, the aim of this study was to evaluate the feasibility and to measure SMABF using transesophageal echocardiography (TEE) during cardiac surgery under hypothermic cardiopulmonary bypass (CPB). Methodology: Thirty-five patients undergoing elective cardiac surgery under CPB were enrolled. Heart rate, mean arterial pressure (MAP), cardiac output (CO), SMABF, superior mesenteric artery (SMA) diameter, superior mesentric artery blood flow over cardiac output (SMA/CO) ratio and arterial blood lactates were recorded at three time intervals. T0: before sternotomy, T1: 30 min after initiation of CPB and T2: after sternal closure. Results: SMA was demonstrated in 32 patients. SMABF, SMA diameter, SMA/CO, MAP and CO-decreased significantly (P < 0.0001) between T0 and T1, increased significantly ( P ≤ 0.001) between T1 and T2 and no significant change (P > 0.05) between T0 and T2. Lactates increased progressively from T0 to T2. Conclusion: Study shows that there is decrease in SMABF during CPB and returns to baseline after CPB. Hence, it is feasible to measure SMABF using TEE in patients undergoing cardiac surgery under hypothermic CPB. TEE can be a promising tool in detecting and preventing splanchnic hypoperfusion during perioperative period.